The Impact of Servant Leadership on Positive Affectivity: Mediating by Career Adaptability - Dalia Khalid Faeq; Bayad Jamal Ali (UKH Journal of Social Sciences, 2022)
Career adaptability (CA) in terms of concern, control, curiosity, and confidence exhibited like a mediator between servant leadership and positive affectivity and is the main focus of the present study's conceptual model. In Sulaymaniyah city in Kurdistan Region of Iraq, hotel workers collected information. Structural equation modeling was used to assess the collected data from five-star hotel workers at Sulaymaniyah. The constructs are meaningful and dependable via exploratory factor analysis with reliability testing. Factor analysis demonstrates high convergent and discriminative validity of the results. A complete mediator linking servant leadership and good effectiveness were found to be the CA. In hotel business, embracing a servant leadership approach may enhance personal resources and improve career adaptability.